Contracts (Akad) in Syari’ah Banking - Hayatul Millah (Fakultas Ekonomi dan Bisnis Islam, 2019)
The various types of contracts applied by Islamic banks can be divided into six groups of patterns, namely; Safekeeping patterns, such as wadi’ah yad amanah and wadi’ah yad dhamamah. Loan patterns, such as qardh and qardhul hasan. Profit sharing patterns, such as Mudharabah and musyarakah. Rental patterns, such as Ijarah and Ijarah bittamlik. Buying and selling patterns, such as murabahah, salam and istishna. Other patterns, such as wakalah, kafalah, hiwalah, ujr, sharf, and rahn. There are two types of contract sharing patterns, such as Musyarakah, Mudharabah, Ijarah adn ijarah muntahiya bittamlik, and in this article will explain about those contract of four.